Spectrophotometric Determination of Molybdenum‐Containing Compounds in Aqueous Glucose Solutions. Issue 9 (9th August 2018) - Spasova, Berta; Kuesters, Christof; Stengel, Bruno; Kraut, Manfred; Brandner, Juergen J.
Abstract: The spectrophotometric determination of molybdenum‐containing compounds in aqueous glucose solutions using pyrazine‐2, 3‐dicarboxylic acid was investigated. Determination of the molybdenum complex with pyrazine‐2, 3‐dicarboxylic acid was performed at λ max = 550 nm. The light absorption of the deeply violet complex follows Lambert‐Beer's law and can be measured with a molar absorptivity in the range of 4414–9020 L mol −1 cm −1 . The presented method is very sensitive and shows good reproducibility for the extinction values. Abstract : Molybdenum very rapidly forms a violet complex with pyrazine‐2, 3‐dicarboxylic acid (chelating agent) and stannous chloride (reducing agent). The absorption of this complex can be utilized for the photometric determination of small amounts of molybdenum‐containing compounds in aqueous glucose solutions. The process is fast, sensitive, and reproducible.